A socioecological taxonomy of determinants to colorectal cancer screening in black men: Insights from a mixed-methods systematic review - P.J. Zaire; E. Miller; A.P. Ewing; J. Hefner; K. Wright; L.H. Smith (Preventive Medicine Reports)
Background: In the United States, African/Black American (henceforth Black) men face significantly higher mortality rates from colorectal cancer (CRC) compared to other gender, racial, and ethnic groups. Although CRC is preventable and treatable with early detection, screening rates among Black men remain low. This study aimed to synthesize existing literature on the barriers and facilitators (determinants) of CRC screening to offer guidance to primary care teams in their efforts to improve screening uptake. Methods: We performed a comprehensive systematic review of full-text, peer-reviewed studies published in English to explore the various determinants influencing CRC screening among Black men. Using key terms like “Black or African American,” “male,” and “colorectal cancer screening,” we searched databases including PubMed, PsychInfo, CINAHL, and Embase, published between 2009 and 2022. Findings: The search identified 1235 articles, with 54 meeting the inclusion criteria. Most studies were cross-sectional, examining determinants across the socioecological system. Key barriers included a lack of CRC screening knowledge, poor patient-provider communication, lack of access to screening, and medical mistrust stemming from systemic racism. Significant facilitators included aging, receiving a provider recommendation, having social support, and effective culturally appropriate outreach strategies. Conclusions: Key themes and significant findings from the review provide actionable strategies for primary care teams. These include enhancing knowledge about CRC screening within the patient population, improving patient-provider interactions, and reducing barriers to accessing screening. Future research should aim to develop culturally appropriate and collaborative preventive care strategies to improve screening adherence and CRC-related outcomes.